Students’ Perspectives on the Use of Padlet Wall in Writing Classes - Nawawi, Muhammad; Utami, Citra Puteri (IJLHE: International Journal of Language, Humanities, and Education, 2024)
Writing is the process of generating ideas and expressing them through statements and paragraphs to communicate indirectly with others. It involves articulating thoughts using written language. Writing skills are a critical component of English language proficiency. These skills enable individuals to convey their thoughts meaningfully and interact effectively through written messages. During the pandemic, online learning created opportunities to integrate digital media into teaching, including writing classes. One such tool is the Padlet Wall, a virtual bulletin board that allows lecturers and students to post notes, links, videos, images, and document files. This research aims to explore students’ perspectives on the use of Padlet Wall in writing classes during online learning. The participants of this study were fifth-semester students, and data collection was conducted using a questionnaire. The research employed a survey method to gather insights into whether students appreciated or disliked using Padlet Wall for writing classes. The findings reveal students’ attitudes toward the use of this digital tool in their learning process.